On Precompactness of a Set in General Local and Global Morrey-Type Spaces - Bokayev, Nurzhan Adilkhanovich; Burenkov, Victor Ivanovich; Matin, Dauren Tulutaevich (Eurasian Mathematical Journal, 2017)
Necessary and sufficient conditions for the precompactness of a set in general local Morrey-type spaces and sufficient conditions for the precompactness of a set in general global Morrey-type spaces are obtained.